2018
DOI: 10.1021/acs.chemrestox.8b00204
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Metal Ion Effects on Human Topoisomerase IIα Inhibition by α-(N)-Heterocyclic Thiosemicarbazones

Abstract: Our previous research has shown that α-(N)-heterocyclic thiosemicarbazone (TSC) metal complexes inhibit human topoisomerase IIα (TopoIIα), while the ligands without metals do not. To find out the structural elements of TSC that are important for inhibiting TopoIIα, we have synthesized two series of α-(N)-heterocyclic TSCs with various substrate ring segments, side chain substitutions, and metal ions, and we have examined their activities in TopoIIα-mediated plasmid DNA relaxation and cleavage assays. Our goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…Piperazine-TSCs based CuC 16 inhibit Top2α [ 101 , 102 ] by a strong interaction with the ATP-binding pocket residues [ 99 ] without ROS production [ 102 ]. Thiazole-TSC CuC 17 and 18 are Top2α catalytic inhibitors [ 103 , 104 ] or poisons [ 105 ]. The highly water-soluble proline-TSC CuC series 19 inhibit Top2α and cell proliferation [ 106 ].…”
Section: Copper Complexes As Topoisomerases Inhibitorsmentioning
confidence: 99%
“…Piperazine-TSCs based CuC 16 inhibit Top2α [ 101 , 102 ] by a strong interaction with the ATP-binding pocket residues [ 99 ] without ROS production [ 102 ]. Thiazole-TSC CuC 17 and 18 are Top2α catalytic inhibitors [ 103 , 104 ] or poisons [ 105 ]. The highly water-soluble proline-TSC CuC series 19 inhibit Top2α and cell proliferation [ 106 ].…”
Section: Copper Complexes As Topoisomerases Inhibitorsmentioning
confidence: 99%
“…14 Other α-(N)-heterocyclic thiosemicarbazones have been synthesized and chelated to different divalent metal ions that display unique activity signatures against TOP2. 6,7,11,16 Copper(II) [Cu(II)] thiosemicarbazone complexes generally display high levels of activity against TOP2. 6,16,17 Not only do these Cu(II) thiosemicarbazone complexes act against TOP2, but previous studies from our group and others have shown that some of the same compounds are active against cancer cell lines at nanomolar to micromolar concentrations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6,7,11,16 Copper(II) [Cu(II)] thiosemicarbazone complexes generally display high levels of activity against TOP2. 6,16,17 Not only do these Cu(II) thiosemicarbazone complexes act against TOP2, but previous studies from our group and others have shown that some of the same compounds are active against cancer cell lines at nanomolar to micromolar concentrations. 7,9−11 Humans have two isoforms of topoisomerase II, IIα and IIβ.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, all clinical TopoII poisons are nonspecific with regard to TopoIIα and TopoIIβ and affect the DNA cleavage activity of both isoforms. ,, However, the contribution of each isoform to the therapeutic effects of drugs is not well understood. , In this regard, both cellular and in vivo studies suggest that TopoIIβ is primarily responsible for generating the breaks in the mixed lineage leukemia ( MLL ) gene that initiate the acute myelogenous leukemias that are associated with etoposide treatment. ,, Strong support for this hypothesis comes from studies with a skin carcinogenesis model, where the incidence of secondary malignancies was curtailed in a TopoIIβ-knockout mouse . Further, TopoIIβ was also related to etoposide-induced DNA sequence rearrangements and double-strand breaks in a murine cell model .…”
Section: Introductionmentioning
confidence: 99%